Gene and Aging - DD Farhud; M Asghari; H Sadighi (Tehran University of Medical Sciences, 2008)
"nCollection of multiple processes that increase the chronological age of an organism leading to death is defined as aging, and even though important, it is poorly understood. Recent research has shown that aging is due to biochemical and genetic changes, in interaction with environmental effects, including diet and nutrition. Most knowledge on aging is based on genetic model system, but its molecular mechanisms are still not very clear. Discoveries in molecular biology have made way to look for candidate genes influencing lifespan. Furthermore, new investigations have stressed on the roles of mitochondria as the major generators and direct targets of reactive oxygen species. This paper reviews some recent literature on genes and aging in model system, then discusses the role of mitochondria and nutrients in human aging.